NEBULIZED BUDESONIDE AS ADD-ON TO STANDARD THERAPY IN CHILDREN AGED 5-14 YEARS WITH ACUTE EXACERBATION OF ASTHMA - DEB, RAHUL; NARWAT, ARVIND; VERMA, SAVITA (International Journal of Current Pharmaceutical Research, 2026)
Objective: Out of the top 20 chronic conditions for global ranking of disability adjusted life years in children, asthma is one of them and specifically in the mid-childhood ages i. e, 5–14 y it ranks amongst the top 10 diseases, so we planned this study to see the efficacy of nebulized budesonide as add-on to standard therapy in children aged 5-14 y with acute exacerbation of asthma. Methods: This was a prospective, randomized, open labelled, interventional study conducted in 5-14 y old patients of moderate to severe asthma having acute exacerbation. Thirty children with acute exacerbation of asthma presenting in the Paediatric department at PGIMS, Rohtak were randomized and assessed for efficacy according to PRAM score. Results: PRAM Score at various follow-up time intervals was recorded in both groups and it was observed that mean±SD of PRAM Score at baseline, at 30 min, at 60 min and at 180 min showed non-significant difference during inter-group comparison. At discharge PRAM score was 0.39±0.50 and 0.32±0.48 in group I and group II respectively. Conclusion: This study showed that both nebulized budesonide as an add-on and standard therapy in children aged 5-14 y with acute exacerbation of asthma showed significant improvement in respiratory status in terms of relief of respiratory symptoms with good safety profile and greater satisfaction with nebulized.